PENGARUH KUALITAS PELAYANAN ACCOUNT REPRESENTATIVE TERHADAP KEPATUHAN FORMAL WAJIB PAJAK ORANG PRIBADI (Studi pada Kantor Pelayanan Pajak Pratama Kolaka) - Mas; Mustafa, Santiadji; Winarni, Fatmawati (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
The objective of this research is to know influence between Account Representative Service to The Formal Compliance of Individual Taxpayer in the Small Taxpayer Office Kolaka. The population are used in this study that individual taxpayers that registered in Small Taxpayers Office Kolakaamounted to 19.286 people, where the number of samples amounted to100 people. The samples in this study using the formula slovin. Data analysis method used is simple linear regression test such as t test with used computer program SPSS 21 for windows.The result of this study show that in partially, Account Representative Servicehave a positive and significant effect to The Formal Compliance of Individual Taxpayer in the Small Taxpayer Office Kolaka.Coefficient determination test showed the value of R Square of 0,693, this shows that the ability of independent variables in explaining the dependent variable is quite good with the coefficient of determination of 69.3%, while the remaining 30.7% is explained by other variables not examined. Keywords : Account Representative Service and Formal Compliance of Individual Taxpayers.